Fractal textures of bovine serum albumin films - Glibitskiy, G. G. (Biophysical Bulletin)
The texture features of the films obtained from solutions of bovine serum albumin (BSA) in the presence of sodium and copper ions are considered. The apparatus for producing films and the absorption spectra of BSA in the UV wavelength range are presented. The films have been received from BSA solutions with concentration of 0.41 mg/ml in the presence of salt NaCl at a concentration of 20 mM and in the presence of salt CuCl2 with concentrations of 0.1 mM and 0.4 mM. Texture films of BSA, human serum albumin and calf thymus DNA are compared. The obtained scale invariant fractal textures are similar to textures which are formed on the films surface from the DNA solutions. Presence in solution of heavy metal ions forming compounds with albumin molecules prevents the formation of scale invariant fractal textures on films from these solutions.